Strategy for Increasing E-WOM-Based Purchasing Decisions on Wardah Products in Indonesia - Nofikasari, Nofikasari; Nurhayati, Nurhayati; Firdaus, Firdaus (International Journal of Economics Development Research (IJEDR), 2024)
Skincare products continue to evolve amidst intense competition in the cosmetics industry, including in Indonesia. Wardah, as one of the leading halal cosmetic brands, is trying to increase its decision in the foundation subcategory through Electronic Word of Mouth (e-WOM) based strategies. The purpose of the research to be carried out is to analyze the influence of halal product perceptions, halal brand awareness, and e-WOM on purchasing decisions for Wardah products. This research utilizes quantitative methods by distributing questionnaires to Wardah consumers in Indonesia. The number of respondents in this study reached 100 people. Data analysis was carried out with the help of smart PLS version 4. From the test findings, it can be seen that the perception of halal products has a positive and significant influence on e-WOM, while halal brand awareness has a significant impact on purchasing decisions. In contrast, e-WOM has no significant effect on purchasing decisions. It is hoped that the findings of this study will help Wardah create a successful marketing plan and serve as a guide for future research in the halal cosmetics industry